Localized public investment and agricultural performance in Malawi: Synopsis - Mwabutwa, Chance (International Food Policy Research Institute, 2017)
This note focuses on how public investments affect crop productivity in Malawi’s districts, and estimates localized public expenditure multipliers. We use these multipliers to analyze whether government expenditures have slowed or accelerated agriculture sector growth, a topic of great interest to public pol-icy makers. Given the relatively large share of government ex-penditure in agriculture sector investment in Malawi, public ex-penditure policies may play an important role in agricultural productivity dynamics.